Development of liqueurs of Curriola (Pouteria ramiflora) native fruit, proximal evaluation and acceptability (Research, Society and Development, 2021)
This study aimed to characterize the centesimal composition of the fruit of the currioleira (Pouteria ramiflora) and to verify the physicochemical and sensorial characteristics of the fruit liqueurs. The levels of moisture, dietary fiber, protein, lipids, ashes and carbohydrates and the energetic value of fruit pulp were quantified. Liqueurs of pulp and whole fruit were prepared with sugar concentrations of 150 and 250g.L-1. The liqueurs were submitted to sensory analysis of acceptance and purchase intention and determined the alcohol content, total acidity, pH, soluble solids, color parameters, total phenolic compounds and antioxidant capacity. In the centesimal composition of the curriola pulp, the high fiber content is 12.75g.100g-1 and low calorie 54.11kcal.100g-1. Significant differences p